2023
DOI: 10.3390/polym15061411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hemp Hurd Biochar and Humic Acid on the Flame Retardant and Mechanical Properties of Ethylene Vinyl Acetate

Abstract: In this work, the combination of biochar produced through a pyrolytic process of hemp hurd with commercial humic acid as a potential biomass-based flame-retardant system for ethylene vinyl acetate copolymer is thoroughly investigated. To this aim, ethylene vinyl acetate composites containing hemp-derived biochar at two different concentrations (i.e., 20 and 40 wt.%) and 10 wt.% of humic acid were prepared. The presence of increasing biochar loadings in ethylene vinyl acetate accounted for an increasing thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…The absence of reaction between PAP and the three flame retardants was confirmed by 31 . Besides, it is reported in the literature that the effect of EX on the complex viscosity is not only due to the establishment of hydrogen bonds but also to metal cations grafted onto polymer chains by a single link [17,19,46,47]. It is reported that the presence of EX in the polyamide lead to corrosion phenomena, potentially due to the formation of free diethylphosphinic acid [17,35].…”
Section: Thermal Stability Of Pap/frs Compounds In the Melt Statementioning
confidence: 99%
“…The absence of reaction between PAP and the three flame retardants was confirmed by 31 . Besides, it is reported in the literature that the effect of EX on the complex viscosity is not only due to the establishment of hydrogen bonds but also to metal cations grafted onto polymer chains by a single link [17,19,46,47]. It is reported that the presence of EX in the polyamide lead to corrosion phenomena, potentially due to the formation of free diethylphosphinic acid [17,35].…”
Section: Thermal Stability Of Pap/frs Compounds In the Melt Statementioning
confidence: 99%
“…The electrical conductivity was related to the evolution of the biochar microstructure (development of graphite-like structure and changes in microporosity) in regard with the thermochemical conversion process parameters [44]. Hemp biochar carbonized at 400-600°C were classified as lignocellulosic materials with a good potential for solid biofuel applications [40][41][42][43][44]54]. Specifically, the resulting carbonized biochar presented low moisture content (below 2.50%) favourable for high fuel quality, low volatile matter (27.1-10.4%) likely to show lower particle matter emissions, limited ash content (6.8-9.8%) resulting in low risk of fouling issues during the combustion, high carbon content (73.8-86.8%) suggesting strong energy density, associated with high higher heating values (28.45-30.95 MJ kg− 1) [40][41][42][43][44].…”
Section: Cannabis Sativa: Hemp Biocharmentioning
confidence: 99%
“…One of the study investigated reinforcing bio-composites by using biochar produced from hemp straw in E-glass fibre in a vinyl-ester polymer matrix [40][41][42][43][44][45][46][47][48][49][50][51]54]. Another study indicated that the addition of biochar in polyvinyl alcohol/biochar composites increased tensile modulus and storage modulus above the glass transition temperature but reduced the tensile strength, increased the thermal decomposition temperature of the composites, and provided to the composites an electrical conductivity similar to the most carbon nanotube and graphene reinforced polyvinyl alcohol composites [40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Cannabis Sativa: Hemp Biocharmentioning
confidence: 99%
See 1 more Smart Citation